New cascaded multilevel converter topology based on basic unit with reduction of DC sources - Ali, J.S.M. (Institute of Electrical and Electronics Engineers Inc., 2015)
Multilevel converters have been considered today as the state of the art of DC/AC power conversion technology for high power medium voltage applications without the negation of power quality. This paper presents a new multilevel converter topology with minimum power electronics switches (IGBTs). This topology has a basic unit of 4 switches with a series/parallel combination of isolated DC sources. The comparison for the required number of switches, power diode, gate driver circuits and voltage stress across the switches of proposed topology with conventional and other novel topologies are discussed. This structure minimizes the total harmonic distortion (THD) in the output voltage waveform with reduced DC source. The operation and validation of the proposed multilevel converter is verified by simulation results of a single-phase 11-level converter. Â© 2015 IEEE.